Teletrabalho no setor público brasileiro: Impacto potencial sobre o tráfego urbano e as emiss\~oes de carbono - Nilo Luiz Saccaro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– In addition to advantages for companies and workers, teleworking could prove a factor on reducing the number of trips, which would contribute to the improvement of many variables of urban traffic. From this perspective, this paper presents an estimation for reducing the number of trips due to the implementation of telework in the Brazilian public sector, as well as estimation of carbon dioxide emissions avoided by this trip reduction. According to them, every 10% of Brazilian government employees that adopt teleworking can result in reduction of up to 0.5% in the annual number of trips made nationwide. The decrease in carbon dioxide emissions resulting from these avoided trips would be about 0.6% of the national total emitted by cars and motorbikes. Thus, encouraging telecommuting may be interesting to urban traffic management policies in Brazil.
Keywords: R41; 330; urban mobility; urban sustainability; traffic; avoided trips